Integrating hemeroby into environmental assessment: Trends and future perspectives - Falko, N.; Tutova, H.; Panchenko, K.; Lisovets, O.; Kunakh, O.; Zhukov, O. (Regulatory Mechanisms in Biosystems, 2025)
Hemeroby is a widely used ecological concept designed to quantify the degree of anthropogenic disturbance in natural ecosystems. Since its introduction in the 1950s, it has evolved into a versatile indicator applicable across various spatial scales, land use types and ecological contexts. Despite its extensive use, the concept is methodologically diverse and is applied inconsistently, which limits its potential for standardized environmental assessment. In this study, we conducted a bibliometric ana l ysis and topic modelling of 228 peer-reviewed articles to identify key research areas and emerging trends in hemeroby-related studies. Five major thematic clusters were identified: (1) landscape-scale disturbance; (2) naturalness assessment; (3) water quality and aquatic vegetation; (4) urban biodiversity; and (5) habitat degradation. The two most influential topics, urban biodiversity and habitat degradation, together account for over 60% of all publications. Latent Dirichlet Allocation (LDA) was employed to explore the thematic structure and relationships between topics. Citation analysis revealed that papers with moderate thematic novelty and interdisciplinary linkages tend to have higher citation rates. Studies focusing on habitat degradation ( topic 5) were the most conceptually cohesive and widely cited due to the consistent application of phytosociological and floristic methods. In contrast, studies on water quality (topic 3) were less integrated into the hemeroby framework and showed lower conceptual cohesion. The concept of hemeroby has become increasingly prevalent in spatial ecological modelling, urban ecosystem assessment and life cycle environmental impact analysis (LCA). Recent advances have emphasized the integration of hemeroby with the functional traits of species, remote sensing and GIS-based land use mapping. Particular attention is given to its role as a proxy for landscape naturalness, and to its usefulness in detecting ecological thresholds, restoration potential and functional degradation in urban and semi-natural systems. The concept has also been adapted for evaluating the impact of human activity on soil (soil hemeroby) and freshwater habitats. However, challenges remain, including subjectivity in expert-based scoring, variability across regional applications and limited taxonomic resolution in certain groups. Future research should focus on standardising evaluation protocols, expanding the range of indicator taxa (e.g. soil fauna and microflora) and integrating hemeroby into broader ecosystem condition and nature-based solution frameworks. Hemeroby thus has great p o tential to inform policy, guide land use planning and enhance the effectiveness of environmental monitoring and biodiversity conservation in the face of increasing anthropogenic pressure.